Strongly almost (w,?)-summable sequences defined by Orlicz functions - Çolak, Rifat; Et, Mikail; Malkowsky, Eberhard (My University, 2005)
The purpose of this paper is to introduce the spaces of sequences that are strongly almost (w,?)-summable with respect to an Orlicz function. We give some relations related to these sequence spaces. It is also shown if a sequence is strongly (w,?)-summable with respect to an Orlicz function, then it is S?-statistically convergent. © 2005 by the University of Notre Dame. All rights reserved.